The Different Strategies for the Radiolabeling of [211At]-Astatinated Radiopharmaceuticals - Jie Gao; Mei Li; Jingjing Yin; Mengya Liu; Hongliang Wang; Jin Du; Jianguo Li (MDPI AG, 2024)
Astatine-211 (211At) has emerged as a promising radionuclide for targeted alpha therapy of cancer by virtue of its favorable nuclear properties. However, the limited in vivo stability of 211At-labeled radiopharmaceuticals remains a major challenge. This review provides a comprehensive overview of the current strategies for 211At radiolabeling, including nucleophilic and electrophilic substitution reactions, as well as the recent advances in the development of novel bifunctional coupling agents and labeling approaches to enhance the stability of 211At-labeled compounds. The preclinical and clinical applications of 211At-labeled radiopharmaceuticals, including small molecules, peptides, and antibodies, are also discussed. Looking forward, the identification of new molecular targets, the optimization of 211At production and quality control methods, and the continued evaluation of 211At-labeled radiopharmaceuticals in preclinical and clinical settings will be the key to realizing the full potential of 211At-based targeted alpha therapy. With the growing interest and investment in this field, 211At-labeled radiopharmaceuticals are poised to play an increasingly important role in future cancer treatment.